The Magic Porridge Pot - Pace, David (Italy : Ladybird books Ltd, 2013)
Based on the classic fairy tale. A little girl is given a magic porridge pot, but one day when her mother forgets to stop it cooking, the whole town is soon filled with porridge! Read it yourself with Ladybird is one of Ladybird's best-selling series. For over thirty-five years it has helped young children who are learning to read develop and improve their reading skills. Each Read it yourself book is very carefully written to include many key, high-frequency words that are vital for learning to read, as well as a limited number of story words that are introduced and practised throughout. Simple sentences and frequently repeated words help to build the confidence of beginner readers and the four different levels of books support children all the way from very first rea..
Keywords: English